Een toeristische brochure: een oefening in persuasieve teksten: Casus: de Nederlandstalige brochure over Zagreb - Pancirov Cornelisse, Željana; Žagar, Ana Marija; Steurs, Frieda (Acta Neerlandica, 2021)
Persuasive documents are defined as documents that transfer the information to the reader with the purpose of influencing their attitude. Travel brochures, like the brochure of the city of Zagreb, the capital of Croatia, also belong to this category. Since tourism plays an important role in Croatia’s economy and since every year the number of Dutch speaking tourists visiting Zagreb is growing, a two-part study was conducted to test whether the Dutch translation of the brochure fulfils its purpose, i.e. whether it is convincing or not. The first part of the study was carried out using Hoeken’s (Het ontwerp van overtuigende teksten) pros-and-cons method. Six subjects participated in the study: three from the Netherlands and three from Flanders, Belgium. The second part of the study consists of authors’ analysis of the brochure based on Hoeken’s method as well. Finally, advice is given on how the brochure could be improved.